Soda lime silica glass with high visible light transmittance
Patent Information
- Application Number
- JP2024205768
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2040-02-03
Smart Images

Figure 2025036425000001 
Figure 2025036425000002 
Figure 2025036425000003
Abstract
Description
[Technical field]
[0001] 2. Background of the Invention TECHNICAL FIELD TO WHICH THEINVENTION BELONGS The present invention describes a soda-lime-silica glass with high visible light transmission, mainly for its use in any presentation (interior, exterior, for glazing, with or without coating) in the building industry, but not limited to other applications such as the automotive industry or appliances, with a visible light transmission of at least 89%, a dominant wavelength (DW) of about 490 to 505 nanometers and a purity (Pe) not exceeding 1% for a controlled thickness of 5.66 mm. [Background technology]
[0002] 2. Description of Related Art Clear glass is of great importance in the building industry due to its main characteristics: high purity and faithfulness to the colors seen through the glass. It is often used in furniture and store windows, exteriors and interiors. Even with thick glass, it can maintain a high visible light transmittance.
[0003] Transparent glass with high visible light transmittance is desirable in order to realize more accurate depiction of objects through glass at a lower cost than currently available commercially available glass.
[0004] Clear glass compositions can be made in a variety of ways. In certain circumstances, clear glasses are produced using raw materials that are low in iron oxide. Some glasses use tin oxide, sodium nitrate, and / or cerium oxide as reducing or oxidizing agents to achieve a particular redox ratio, and cobalt and chromium as colorants. Others do not contain sodium sulfate to avoid polysulfide formation and yellowing, and some use cerium oxide as a decolorizing agent.
[0005] Dolomite is an anhydrous carbonate mineral containing calcium and magnesium carbonate. It crystallizes in a triangular rhombohedral crystal system, forming colored crystals. In the solid state, it exists as ankerite, which is mainly composed of iron, and kutsunophorite, which is mainly composed of manganese. When it contains trace amounts of iron, the crystals become yellow to brown in color.
[0006] Iron can exist in two different oxidation states in glass (silica-sodium-calcium): Fe 2+ is ferrous oxide (FeO), Fe 3+ are present in glass as ferric oxide (Fe2O3). Each ion has different properties. Ferrous ions have a broad and strong absorption band centered at 1050 nm, reducing infrared radiation. This absorption band also extends into the visible light range, reducing light transmittance and giving glass a bluish tint. Ferric ions have a strong absorption band in the ultraviolet range, which prevents light from passing through the glass, and two weak absorption bands in the visible range of 420-440 nm, which slightly reduce light transmittance and give glass a yellow color.
[0007] The balance of ferrous and ferric oxides directly affects the color and transmittance properties of the glass.
number
[0008] The iron redox ratio is the amount of ferrous iron (FeO) divided by the total iron (Fe2O3). 3+ The more ferrous ions (Fe ) there are, the higher the absorption rate of ultraviolet rays, the higher the light transmittance, and the yellower the color. 2+ ) increases, the absorption rate of infrared rays increases, but the absorption rate of ultraviolet rays decreases, and the light transmittance also decreases. [ka]
[0009] The color of the glass changes as the concentration of FeO changes relative to Fe2O3. The color transition can go from yellow through green to blue to amber. From the blue, the amber color of the glass is given by the formation of iron polysulfides under high redox conditions. The color changes as follows (based on experimental results): Yellow - Low Redox (0.12) - High Light Transmission (High Iron Ion) Yellow-green (0.16) Green-yellow (0.20) Green (representative value of green glass: 0.25) Bluish Green (0.29) Greenish Blue (0.35) Blue (0.50) Olive Green (0.60) Champagne (0.65) Amber - High Redox (0.75) - Low Light Transmission (Low Iron Ions)
[0010] To control the balance between ferrous and ferric oxides, the batch conditions and melting atmosphere must be adjusted. In the first case, the concentrations of reducing agents such as carbon or tin oxide and oxidizing agents such as sodium sulfate are adjusted. For the melting conditions, the furnace atmosphere with varying oxygen excess and the flame arrangement during combustion must be adjusted depending on the thermal performance and the desired glass hue.
[0011] Sodium sulfate (Na2SO4) is added to the batch as a raw material. It is mainly used as a high-temperature refining agent, as an antifoaming agent, to promote mass transport, to dissolve free silica on the glass surface, and to reduce solid inclusions.
[0012] On the other hand, sodium sulfate has an oxidizing effect, so a small amount of carbon is usually added to prevent unnecessary oxidation and at the same time lower the reaction temperature.
[0013] During glass manufacturing, Na2SO4, the main component of sulfur in glass, is converted to SO3, which controls the conversion of Fe2O3 to FeO. However, the presence of SO3 in the final glass does not affect the glass's ability to transmit visible light. The amount of SO3 dissolved in glass is reduced in the presence of: 1. The amount of sodium sulfate is small (proportionally). 2.High melting property. 3.Long melting time. 4. The furnace environment is more oxidizing. 5. The reduction of iron to ferrous oxide is more rapid (more Fe 2+ ; less Fe 3+ ), with a minimum of 70-75% Fe 2+ Reached.
[0014] Therefore, the amount and effect of SO3 in a glass batch must be balanced according to the amount of carbon present in the glass batch.
[0015] Furthermore, it is common knowledge that the amount of SO3 in a glass batch must be within a certain critical amount, since a small amount of SO3 in the glass batch affects the refining characteristics, i.e., the ability to remove bubbles in the melting furnace.
[0016] The first reducing agent is tin oxide (SnO2) (D. Benne et al. in the paper, “The effect of alumina on the Sn 2+ / Sn 4+ (Referring to “redox equilibrium and the incorporation of tin in Na2O / Al2O3 / SiO2 melts” Journal of Non-Crystalline Solids. 337, 2004, 232-240). Tin in contact with molten glass diffuses into the glass in an oxidized state and also interacts with other polyvalent elements such as iron and chromium. At high temperatures, tin is reduced to Sn 2+ , oxidation state Sn 4+ This shows that the oxygen is in equilibrium with the dissolved oxygen in the melt. [ka]
[0017] The above has to do with the ability of tin to transfer two electrons to iron, a reaction that occurs early in the glass melting process when tin is heated and reduced. [ka]
[0018] Then, during the cooling stage, the ions Sn 2+ +2e - Two ferric irons, Fe 3+ ions into two ferrous Fe 2+ Reduce to ions. [ka]
[0019] Part of the redox balance is achieved by using reducing substances such as carbon, which exists as ordinary coal or low-iron graphite, to interact with iron and sulfur. Large amounts of carbon interact with iron and reduce it to form iron sulfide, which can give the glass its amber hue. 2+ Make it into the shape of:
[0020] Titanium dioxide also functions as a colorant, and when used in combination with Fe2O3, it functions as a colorant. The most stable form of titanium in glass is the tetravalent form (Ti 4+) M.D. Beals, “Effects of Titanium Dioxide in Glass”, The glass industry, September 1963, pp 495 - 531, discusses the interest shown in titanium dioxide as a component of glass. The effects of titanium dioxide are commented to be a large increase in the refractive index of TiO2, an increase in the absorption of ultraviolet light, and a decrease in viscosity and surface tension. Data on the use of titanium dioxide in enamels indicate that it increases the chemical durability of TiO2 and acts as a flux. Transparent glasses containing titanium dioxide can be found in all the common glass-forming systems (borate, silicate, phosphate). The various areas of glass formation in titanium dioxide-containing systems are not summarized in one place, as the discussion is based on properties rather than on the applications of titanium dioxide-containing glasses alone.
[0021] There is literature on colored glass compositions with infrared and ultraviolet absorbing properties. W. A. Weyl in the book “Coloured Glasses, Society of Glass Technology”, reprinted 1992, describes the various theories on glass colour related to the current view on the structure and composition of glass. In this book, the use of chromium and its compounds for colouring glass is described. In the glass industry, chromium is added to the raw materials to obtain the emerald green colour, which is called Cr 3+ Chromium is the typical color of Cr 6+ or CrO4 2- When present as Cr, it becomes pale yellow. 2+ When present as such, emerald green is obtained.
[0022] CR Bamford explains the principles, methods and applications of coloring glass in his book “Colour Generation and Control in Glass, Glass Science and Technology”, Elsevier Science Publishing Co., Amsterdam, 1977: the colour of the incident light, the interaction of the glass with the light, and the interaction of the transmitted light with the observer’s eye. The procedure requires the spectral transmittance data of the glass at the relevant glass thickness and viewing angle.
[0023] In the paper Gordon F. Brewster, et al., “The color of iron containing glasses of varying composition”, Journal of the Society of Glass Technology, New York, USA, April 1950, pp 332 - 406, the color change due to systematic composition variation in iron-containing silica glasses and silica-free glasses is evaluated in terms of visual color, spectral transmittance and chromaticity.
[0024] Other papers also discuss the importance of the equilibrium between ferrous and ferric oxides in glass, such as NE Densem, “The equilibrium between ferrous and ferric oxides in glasses”, Journal of the Society of Glass Technology, Glasgow, England, May 1937, pp. 374 - 389; JC Hostetter and HS Roberts, “Note on the dissociation of ferric oxide dissolved in glass and its relation to the color of iron-bearing glasses”, Journal of the American Ceramic Society, USA, September 1921, pp. 927 - 938.
[0025] U.S. Patent No. 4,792,536 (Pecoraro et al.) relates to blue glass compositions that use reducing conditions to enhance the iron state of the iron oxide, with non-transparent blue tint glass, compositions having at least 0.45% by weight iron expressed as Fe2O3, at least 35% of the iron state expressed as FeO, and a visible light transmission of at least 70% being preferred. The patent also discloses low-iron, and high-iron, high redox soda-lime-silica glass compositions produced in a multi-stage melting and vacuum-assisted refining operation, or those produced in a conventional float glass system.
[0026] U.S. Patent No. 6,313,053 (Shelestak) discloses the use of proportions of colorants of iron, cobalt, and optionally chromium to obtain a glass having the desired blue color and spectral characteristics, with about 0.40 to 1.0 percent Fe2O3, about 4 to 40 ppm CoO, and optionally 0 to about 100 ppm Cr2O3, a redness greater than 0.35 to about 0.60, and a light transmittance of at least 55% at a thickness of about 0.154 inches, other components of the composition include up to about 0.3 wt% SO3, 0 to about 0.5% Nd2O3, 0 to about 0.5% ZnO, 0 to about 3 ppm Se, 0 to about 0.1 wt% MnO2, 0 to about 1.0 wt% CeO2, 0 to about 0.5 wt% TiO2, and 0 to about 2.0 wt% SnO2. This patent also discloses currently available methods for manufacturing glass, which are specifically limited to maintaining the redox ratio of the glass in the range of 0.02 to 0.06.
[0027] U.S. Patent Application Publication No. 2007 / 0213197A1 (Boulos et al.), incorporated herein by reference, discloses that a colored glass composition is proposed with a colorant composition including 0.4-0.6 wt. % Fe2O3, 0.18-0.28 wt. % FeO, 0.05-0.3 wt. % MnO2, and 0-8 ppm CoO to adjust the aqua blue color, and is used with a dominant wavelength of 489.2 nm + / - 1.2 nm, a redox ratio in the range of about 0.40 to about 0.58, an excitation purity of 7% + / - 1%, and an infrared transmittance in the range of 16% to 29% at a thickness of 4.0 mm.
[0028] U.S. Patent No. 5,030,594 (Heithoff) discloses that a transparent glass with a light transmission of 87% or more can be obtained with a blue-tinged hue, produced in a multi-stage melting and vacuum-assisted refining system. The glass composition uses very small amounts of iron oxide and an iron state of at least 0.4, sodium sulfate is limited to 0.05 percent expressed as SO3, and the batch materials are free of limestone and dolomite, aragonite being used instead.
[0029] U.S. Patent No. 6,218,323 (Bretschneider et al.), incorporated herein by reference, proposes a neutrally colored glass having 0.1-1 ppm of CoO, ≦0.03 wt. % of Fe2O3, and a colorant fraction of ≦0.4 FeO / Fe2O3, preferably 0.3, a soda-lime-silica base composition is used, the glass having a light transmission of at least 89% (illuminance D65 according to DIN 67 507) at a nominal thickness of 4 mm.
[0030] U.S. Patent No. 6,962,887 (Heithoff), incorporated herein by reference, describes a clear glass having a blue edge tint produced in an oxy-fuel, non-vacuum float glass system, the tint portion comprising 0-02 wt.% Fe2O3, 0-01 wt.% NdO, and 0-03 wt.% CuO, with 0-5 ppm CoO, 0-01 wt.% Nd2O3, 0-03 wt.% CuO, retained sulfur of 0.11 wt.% or less SO3, a redox ratio in the range of 0.3-0.6, and an oxidizer comprising at least one of sodium nitrate and cerium oxide. The resulting glass has a dominant wavelength in the range of 485 nm to 505 nm at an edge thickness of 5.5 mm.
[0031] U.S. Patent 6,548,434 (Nagashima) proposes a light-colored, high-transmittance glass (herein incorporated by reference) containing, as coloring components, less than 0.06% Fe2O3, 0.5 to 5 ppm CoO, and 0 to 0.45% CeO2 by weight percent; where the proportion of FeO in terms of total iron (Fe2O3) is less than 40%, the glass has a dominant wavelength of 470 to 495 nm at a thickness of 10 mm for light blue tones and 560 to 585 nm for neutral gray or bronze tones. The glass also contains 0.05 to 0.25% SO3 and 0.001 to 1 wt% of at least one heavy element oxide from the group Y, La, Zr, Hf, Nb, Ta, W, Zn, Ga, Gc, Sn to avoid the formation of NiS.
[0032] U.S. Pat. No. 8,361,915 (Cid-Aguilar et al.), incorporated herein by reference, proposes a transparent glass containing, in weight percent, about 0.005 to about 0.08% ferric oxide, 0.00002 to about 0.0004% Se, 0 to about 0.003 to about 0.0010% CoO, 0.01% wt. CuO, about 0.6 to about 0.6 CeO2, about 0.02 to about 1.0 TiO2, and about 0 to about 2 NaNO3, the transparent glass having a visible light transmittance of at least 87%, an ultraviolet light transmittance of 85% or less, and a direct solar transmittance of 90% or less.
[0033] U.S. Patent No. 8,962,503 (Nagai et al.), incorporated herein by reference, proposes a colored glass sheet having a total sulfur percentage calculated as SO3 of 0.025-0.065% and a total tin percentage calculated as Fe2O3, SnO2 of 0.001-5.0%, whereby the transmitted light has a blue or green color.
[0034] U.S. Patent No. 10,011,521B2 (Nagai et al.) describes a colored glass using Fe2O3 as the main colorant, which is described as providing blue or green transmission in a proportion of 0.001 to 5.0% calculated as total iron Fe2O3. The main use of SO3 is as a fining agent for molten glass, with a total sulfur proportion of 0.005 to less than 0.025% for a thickness of 4 mm, and the use of SnO2 in this glass is described as a buffer for the oxidation-reduction reaction of iron and sulfur, with a tin proportion of 0.001 to 5.0%. The glass of this patent has a solar transmittance T of 0.001 to 0.5% for a thickness of 4 mm as defined by JIS R3106 (1998). e Up to 65%, light transmittance T v (Illuminance A, 2° field of view) Maximum 60%. Summary of the Invention
[0035] It would be advantageous to provide a soda-lime-silica glass that has high visible light transmittance. Additionally, it would be advantageous to provide a method for producing low iron soda-lime-silica glass that can be used regardless of the type of heating system or furnace used to melt the glass batch materials, eliminating the limitations associated therewith.
[0036] Summary of the Invention According to the present invention, a purity (Pe) of 1% or less for a thickness control of 5.66 mm and a high visible light transmittance (L) of at least 89% at a dominant wavelength (DW) of about 490 to 505 nanometers are obtained. tC A glass or glass sheet is provided having a soda-lime-silica glass composition having a total iron oxide (Fe2O3) of 0.02 to 0.06 wt%; 0.006 to 0.02 wt% FeO (ferrous iron); about 0.30 to 0.55 redox (FeO / Fe2O3); about 0.3 to 10 ppm Cr2O3; about 50 to 500 ppm TiO2; about 10 to 500 ppm SnO2; and a critical amount of about 0.10 to 0.25 wt% SO3.
[0037] A primary object of the present invention is to provide a transparent glass composition having high visible light transmittance.
[0038] Another object of the present invention is to provide a low cost clear glass. This can be achieved by using low iron raw materials such as low iron dolomite and using a mixture of clear and low iron cullet to achieve the proper balance of concentration of colorants such as Cr2O3, TiO2 and Fe2O3. Also, by partially replacing low iron raw materials other than low iron dolomite with conventional raw materials, the colorant concentration of Cr2O3, TiO2, Fe2O3, etc. can be achieved by using conventional sand that contains these oxides as impurities.
[0039] Further non-limiting embodiments or aspects are defined and described in the following sections.
[0040] Clause 1: A transparent glass having a soda-lime-silica glass composition comprising: total iron oxide (Fe2O3) of 0.02-0.06 wt.%; ferrous iron (FeO) of 0.006-0.02 wt.%; redox (FeO / Fe2O3) of about 0.30 to 0.55 wt.%; Cr2O3 of about 0.3 to 10 ppm; TiO2 of about 50 to 500 ppm; SnO2 of about 10 to 500 ppm; and SO3 of about 0.10 to 0.25 wt.%.
[0041] Clause 2: The transparent glass of clause 1, wherein the low iron oxide content is achieved by partial replacement of normal raw materials with low iron raw materials and / or by complete replacement of normal dolomite with low iron dolomite, the low iron dolomite having a maximum iron oxide concentration of 0.020 wt.%.
[0042] Clause 3: At least 89% visible light transmittance (L tC ), a dominant wavelength (DW) of about 490-505 nanometers and a purity (Pe) of 1% or less, characterized in that the glass has a thickness in the range of 2-19 mm.
[0043] Clause 4: When the transparent glass has a controlled thickness of about 5.6 mm or more and 25 mm or less, it has a visible light transmittance (L) of at least 89%. tC 4. The transparent glass of any one of claims 1 to 3, having a dominant wavelength (DW) of about 490 to 505 nanometers and a purity (Pe) not exceeding 1%.
[0044] Clause 5: The transparent glass of any of clauses 1 to 4, wherein the glass has a thickness of 1.0 mm to 25 mm, preferably 2.0 mm to 19 mm, more preferably 2.0 mm to 10 mm, and most preferably 2.0 mm to 6.0 mm.
[0045] Clause 6: A transparent glass according to any one of clauses 1 to 5, wherein the glass is flat glass.
[0046] Clause 7: A method for producing clear glass using a conventional float non-vacuum glass system, comprising the steps of: providing a glass batch, the glass batch comprising low iron dolomite in the range of 5-20 wt%, the low iron dolomite constituting a maximum total iron content of 0.030 wt%, preferably 0.025 wt%, more preferably 0.022 wt%, expressed as Fe2O3; melting the glass batch to provide molten glass; flowing the molten glass onto a molten tin bath; moving the glass on a surface of the molten tin bath while controllably cooling the molten glass and applying forces to the glass melt to provide glass of a desired thickness and width; and removing the glass from the molten tin bath.
[0047] Clause 8: The method of clause 7, wherein the melting step is carried out in a furnace having combustion, the furnace being an air-fuel furnace or an oxy-fuel furnace, and the combustion controls the oxidation-reduction (FeO / Fe2O3) in the glass to about 0.30-0.55 wt%.
[0048] Clause 9: The method of clauses 7 or 8, additionally comprising mixing the low-iron dolomite with cullet, sand, soda ash, limestone, salt cake, coal, graphite, or combinations thereof. Clause 10: The method of any of clauses 7 to 9, wherein the low-iron dolomite further comprises calcium oxide and magnesium oxide.
[0049] Clause 11: The method according to any one of clauses 7 to 10, wherein the oxidation-reduction is controlled by carbon, a reducing agent such as tin oxide, and an oxidizing agent such as sodium sulfate.
[0050] Clause 12: Transparent glass is: [Table 12] Including, At least 89% visible light transmittance (L tC12. The method of any of clauses 7 to 11, comprising providing a transparent glass sheet having a dominant wavelength (DW) of about 490 to 505 nanometers and a purity (Pe) of 1% or less, the glass having a thickness of 2 to 19 mm.
[0051] Clause 13: The method of any of clauses 7 to 12, wherein the low-iron dolomite contains up to 0.020 wt% total iron expressed as Fe2O3.
[0052] Clause 14: The method of any of clauses 7 to 13, further comprising adjusting the oxygen or air in the furnace to produce a glass having a redox (FeO / Fe2O3) of 0.30 to 0.55.
[0053] Clause 15. The method of any of clauses 7 to 14, wherein the low-iron dolomite further comprises 5 to 15 wt.% CaO and 2 to 10 wt.% MgO.
[0054] Clause 16: The method of any of clauses 7 to 15, wherein the process for producing glass is changed from one of the glass batch portions to another of the glass bath portions by changing the weight percentage of tin and / or tin-containing compounds to change the weight percentage of total iron within a range specified for the glass batch portions being changed.
[0055] Clause 17. The method of any of clauses 7 to 16, wherein the glass batch further comprises a low iron raw material selected from the group consisting of low iron sand, low iron calcite, low iron cullet, low iron graphite, and combinations thereof.
[0056] Clause 18: The method of any of clauses 7 to 17, wherein the method further comprises using carbon and tin oxide as reducing agents.
[0057] Clause 19: The method of any of clauses 7 to 18, wherein the method further comprises using sodium sulfate as an oxidizing agent.
[0058] Clause 20: A method of forming clear glass using a conventional float non-vacuum glass system, comprising: providing a glass batch; melting the glass to provide a pool of molten glass; flowing the molten glass onto a molten tin bath; moving the molten glass over a surface of the molten tin bath while controllably cooling the glass to apply a force to the glass to provide glass of a desired thickness and a desired width; and removing the glass from the molten tin bath, wherein the glass is formed using the following raw materials alone or in combination in the amounts: [Table 20]
[0059] Clause 21: The method of clause 20, wherein the composition comprises sand having a maximum Fe2O3 content of 0.010%, calcite having a maximum Fe2O3 content of 0.010%, low-iron graphite having a maximum Fe2O3 content of 0.010%, or cullet having a maximum Fe2O3 content of 0.010%.
[0060] Clause 22. The method of any of clauses 20 or 21, wherein the glass comprises SiO2 in the range of 68 to 75 wt%, preferably 70 to 74 wt%, more preferably 71 to 74 wt%, and most preferably 72 to 74 wt%.
[0061] Clause 23. The method according to any of clauses 20 to 22, wherein the glass has a redox (FeO / Fe2O3) ratio in the range of 0.25 to 0.55, preferably 0.27 to 0.48, more preferably 0.30 to 0.47, and most preferably 0.35 to 0.46.
[0062] Clause 24. The method of any of clauses 20 to 23, wherein the glass has Na2O in the range of 10 to 15 wt%, preferably 12 to 14 wt%, more preferably 13 to 14 wt%, and most preferably 13.8 to 14.0 wt%.
[0063] Clause 25. The method of any of clauses 20 to 24, wherein the glass comprises SO3 in the range of 0.1 to 0.3 wt%, preferably 0.15 to 0.25 wt%, more preferably 0.17 to 0.22 wt%, and most preferably 0.18 to 0.21 wt%.
[0064] Clause 26: The glass has a color a in the range of 1.0 to -1.0, preferably 0.0 to -0.8, more preferably 0.0 to -0.5, and most preferably 0.0 to -0.4. * and b in the range of 1 to -1, preferably 0.5 to -0.5, more preferably 0.3 to -0.2, and most preferably 0.2 to -0.1. * 7. A transparent glass according to any one of clauses 1 to 6,
[0065] Clause 27: The glass has a color a in the range of 1.0 to -1.0, preferably 0.0 to -0.8, more preferably 0.0 to -0.5, and most preferably 0.0 to -0.4. * and b in the range of 1 to -1, preferably 0.5 to -0.5, more preferably 0.3 to -0.2, and most preferably 0.2 to -0.1. * 26. The method according to any one of clauses 20 to 25, comprising:
[0066] Article 28. Glass, including: [Table 28]
[0067] Clause 29: Glass, including: [Table 29]
[0068] Clause 30: Glass, including: [Table 30]
[0069] Clause 31: Glass, including: [Table 31]
[0070] Clause 32: The glass according to any one of Clauses 28 to 31, further comprising 50 to 500 ppm TiO2, preferably 75 to 450 ppm TiO2, more preferably 90 to 400 ppm, and most preferably 100 to 390 ppm TiO2.
[0071] Clause 33: The glass according to any one of clauses 28 to 32, further comprising 0.1 to 7 ppm Cr2O3, preferably 0.3 to 6 ppm Cr2O3, more preferably 0.5 to 5.7 ppm Cr2O3, and most preferably 0.6 to 5.6 ppm Cr2O3.
[0072] Clause 34: The glass according to any of clauses 28 to 33, further comprising 25 to 500 ppm SnO2, preferably 35 to 450 ppm SnO2, more preferably 40 to 420 ppm SnO2, and most preferably 47 to 414 ppm SnO2.
[0073] Clause 35: Glass according to any of clauses 28 to 34, further comprising the following features: a light transmittance (L ) of at least 85%, preferably at least 88%, more preferably at least 89%, most preferably at least 89.9%. tC ); ultraviolet transmittance (T) of less than 90%, preferably less than 88%, more preferably less than 86%, and most preferably less than 85.4%; uv ); Infrared transmittance (T ir ) is less than 90%, preferably less than 88%, more preferably less than 86%, and most preferably less than 85.2%; Total Solar Energy Transmittance (TSET) is at most 92%, preferably at most 90%, more preferably at most 89%, and most preferably at most 88.7%; Lightness value (L * ) is 90 to 99; preferably 92 to 98; more preferably 95 to 97; most preferably 96 to 966.3_; a * color channels in the range of 1 to -2, preferably 0.5 to -1.5, more preferably 0 to -1, and most preferably -0.4 to -1.0; *a color channel of 1 to -1, preferably 0.5 to -0.5, more preferably 0.3 to -0.2, and most preferably 0.2 to -0.1; a dominant wavelength of 470 to 525 nm, preferably 475 to 520 nm, more preferably 480 to 515 nm, and most preferably 490 to 505 nm; and a purity (Pe) of 2% or less, preferably 1% or less, more preferably .6% or less, and most preferably 0.5% or less.
[0074] Clause 36: A method of forming transparent glass comprising the step of mixing raw materials, the raw materials comprising cullet, sand, soda ash, salt cake, limestone and dolomite, the dolomite comprising: [Table 36] A method for forming transparent glass comprising the steps of melting raw materials to form molten glass; flowing the molten glass onto a molten tin bath; applying forces to the molten glass by moving the molten glass over the surface of the molten tin bath while controllably cooling the molten glass to form glass of a desired thickness and width; and removing the glass from the molten bath.
[0075] Clause 37: The method of clause 36, wherein the ingredients are present in the following amounts: [Table 37]
[0076] Clause 38: The method of any one of clauses 36 or 37, wherein the sand comprises: [Table 38]
[0077] Clause 39: The method of any of clauses 36 to 38, wherein the salt cake comprises: [Table 39]
[0078] Clause 40: The method of any of clauses 36 to 38, wherein the cullet comprises: [Table 40]
[0079] Clause 41: The method of any one of clauses 36 to 40, wherein the limestone comprises: [Table 41]
[0080] Clause 42: The method of any one of clauses 36 to 41, wherein the soda ash comprises: [Table 42]
[0081] Clause 43. The method of any of clauses 36 to 42, wherein the feedstock further comprises coal or graphite.
[0082] Clause 44: The method of clause 43, wherein the coal or graphite is in the range of 0.01 to 0.3 wt.%; preferably 0.02 to 0.2 wt.%; more preferably 0.03 to 0.1 wt.%; most preferably 0.04 to 0.08 wt.%.
[0083] Clause 44: The method of clause 43 or 44, wherein the coal or graphite comprises: [Table 44] [Brief description of the drawings]
[0084] Brief description of the drawings [Figure 1] 1A and 1B are horizontal cross-sectional views of a glass melting furnace that can be used in the practice of the present invention, with FIG. 1A being the melting section of the furnace and FIG. 1B being the refining and homogenizing section of the furnace.
[0085] [Diagram 2] FIG. 2 is a vertical cross-sectional view of the fusion zone shown in FIG. 1A.
[0086] [Diagram 3] FIG. 3 is an elevational view showing a partial cross section of a glass melting and refining apparatus that can be used in carrying out the present invention.
[0087] [Figure 4] FIG. 4 is a fragmentary side view of a glass ribbon supported on a bath of molten tin. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0088] Description of the Invention As used in the following discussion, unless otherwise indicated, all numerical values expressing dimensions and the like used in the specification and claims are to be understood in all instances to be modified by the term "about". Thus, unless otherwise indicated to the contrary, the numerical values set forth in the following specification and claims may vary depending on the desired properties sought to be obtained by the present invention. At the very least, and without attempting to limit the application of the doctrine of equivalents to the scope of the claims, each numerical parameter should be construed at least in light of the number of reported significant digits and by applying ordinary rounding techniques. Furthermore, all ranges disclosed herein should be understood to include the beginning and ending values of the range and to encompass any and all subranges subsumed therein. For example, the range "1-10" is to be considered to include all ranges between the minimum value of "1" and the maximum value of "10", i.e., all ranges beginning with a minimum value of 1 or more and ending with a maximum value of 10 or less, e.g., "5.5-10". Furthermore, all documents (such as issued patents and patent applications) referred to herein are to be deemed to be "incorporated by reference" in their entirety.
[0089] References to compositional amounts are in "wt %" based on the total weight of the final glass composition unless otherwise indicated. The "total iron" content of the glass compositions disclosed herein is expressed in units of Fe2O3, according to standard analytical methods, regardless of the form actually present. Similarly, the amount of iron in the ferrous state is reported as FeO, even though it may not actually be present in the glass as FeO. The terms "redox", "redox ratio", or "iron redox ratio" refer to the amount of iron in the ferrous state (expressed as FeO) divided by the amount of total iron (expressed as Fe2O3). As used herein, soda-lime-silica glasses having total iron (expressed as Fe2O3) in the range of 0 to greater than 0.06 wt % are low iron soda-lime-silica glasses. Generally, without being limiting to the present invention, high iron soda-lime-silica glass has a total iron content in the ranges of: 0.10 wt% to 2.0 wt% or greater; 0.10 wt% to 1.5 wt% or greater; 0.10 wt% to 2.0 wt%; and 0.10 wt% to 0.80 wt%.
[0090] As can now be understood, the present invention is directed to the production of low iron, high redox soda-lime-silica glasses and is not limited to optical properties, such as UV-Visible and IR transmittance and absorption, and glass color and physical properties, such as glass thickness. In defining non-limiting embodiments of the glasses of the present invention, reference can be made to specific ranges or values of UV, Visible and IR transmittance and absorption, and glass color, and physical properties, such as glass thickness, to identify particular glasses of the present invention and / or glasses produced by the practice of the present invention. Presented below are common additives, such as color additives, that are added to glass batch materials and / or molten glass to alter the optical and physical properties of the glasses of the present invention.
[0091] The “sulfur” content of the glass compositions disclosed herein is expressed as SO3 in accordance with standard analytical methods, regardless of the form actually present.
[0092] As used herein, "visible transmittance" and "dominant wavelength" values are determined using conventional CIE illuminance C and a 2 degree observer angle. One skilled in the art will appreciate that even if the actual thickness of a measured glass sample differs from the standard thickness, properties such as visible transmittance and dominant wavelength can be calculated for an equivalent standard thickness, e.g., 5.5 millimeters ("mm").
[0093] As will be appreciated, the present invention is not limited to the color additives described above, and any color additive to soda-lime-silica glass known in the art may be used in the practice of the present invention, such as, but not limited to, a color additive selected from the group including CoO, Se, NiO, Cl, V2O5, CeO2, Cr2O3, TiO2, Er2O3, MnO2, La2O3, and combinations thereof.
[0094] As can now be understood, the present invention is not limited to the practicing processes and / or apparatus for producing the glasses of the present invention, and any of the glass making processes and / or apparatus known in the art can be used in the practice of the present invention.
[0095] 1 and 2, as necessary, a conventional continuous feed, cross-tank firing, glass melting and non-vacuum refining furnace 20 is shown having an enclosure formed by a refractory containing bottom 22, roof 24, and side walls 26. Glass batch material 28 is introduced at an inlet opening 30 in an extension 32 of the furnace 20, known as a packed dog house, in any convenient or conventional manner to form a blanket 34 that floats on the surface 36 of molten glass 38. The general progression of the glass as shown in FIGS. 1A and 1B is from left to right in the figures toward the inlet end of a glass forming chamber 40 of the type used in the art to make float sheet glass.
[0096] Flames (not shown) for melting the batch materials 28 and heating the molten glass 38 emanate from burner ports 42 spaced along the sidewall 26 (see FIG. 2) and are directed onto and across the surface 36 of the molten glass 38. During the first half of the heating cycle, flames emanate from nozzles 43 (see FIG. 2) in each of the ports on one side of the tank 20 as the furnace exhaust travels through the port on the opposite side of the furnace. During the second half of the heating cycle, the functions of the ports are reversed, with the exhaust port becoming the firing port and the firing port becoming the exhaust port. Firing cycles for furnaces of the type shown in FIGS. 1 and 2 are well known in the art. As can be appreciated by those skilled in the art, the present invention contemplates the use of a mixture of air and fuel gas, or a mixture of oxygen and fuel gas, to generate the flame for heating the batch materials and molten glass. For a discussion of the use of oxygen and fuel gas in furnaces of the type shown in FIG. 1, reference may be made to U.S. Pat. Nos. 4,604,123, 6,962,887, 7,691,763 and 8,420,928, which are incorporated herein by reference.
[0097] The glass batch material 28 as it travels downstream from the batch feed end or dog-house end wall 46 is melted in the melting section 48 of the furnace 20, and the molten glass 38 travels through a waist 54 of a refining section 56 of the furnace 20. In the refining section 56, gas bubbles in the molten glass 38 are removed and the molten glass 38 is mixed or homogenized as it passes through the refining section 56. The molten glass 38 is delivered from the refining section 56 in any convenient or conventional manner onto a pool of molten metal (not shown) contained in a glass forming chamber 40. As the delivered molten glass 38 travels within the glass forming chamber 40 over the pool of molten metal (not shown), the molten glass is sized and cooled. A dimensionally stable sized glass ribbon (not shown) travels from the glass forming chamber 40 to an annealing layer (not shown). Glass manufacturing apparatus of the type shown in Figures 1 and 2, and the type described above, are well known in the art.
[0098] Illustrated in FIG. 3 is a continuous feed glass melting and vacuum refining apparatus 78 for melting glass batch material and refining molten glass. Batch material 80, preferably in a comminuted state, is fed into a cavity 82 of a liquefaction vessel, e.g., a rotating drum 84. A layer 86 of batch material 80 is held against the inner wall of vessel 84 with the aid of the rotation of the drum and acts as an insulating lining. When batch material 80 on the surface of lining 84 is exposed to heat in cavity 82, it forms a liquefied layer 88 which flows out of a central drain opening in the bottom 92 of vessel 84 into a melting vessel 94 to complete the melting of unmelted particles in the liquefied material coming from vessel 84.
[0099] A valve 96 controls the flow of material from the melting vessel 94 into a generally cylindrical, upright vessel 98 having an internal ceramic refractory lining (not shown) that is covered by a gas-tight, water-cooled casing 100. A molten stream 102 of refined glass falls freely from the bottom of the refining vessel 98 and may be passed to subsequent stages of the glass making process. For a detailed discussion of the operation of the apparatus 78 shown in Figure 3, reference may be made to U.S. Patent No. 4,792,536.
[0100] The glasses of the present invention can be produced using any known glass manufacturing process. For example, and not by way of limitation, the low iron, high redox glasses of the present invention can be produced in a multi-stage melting and vacuum-assisted refining operation as shown in FIG. 3. The refining step of this known process is carried out under vacuum to reduce the concentration of dissolved and volatile gas components, particularly sulfur-containing components. As will be appreciated by those skilled in the art, it may be advantageous to remove sulfur-containing components from certain float glass compositions, since the combination of sulfur and iron in the glass can result in amber coloration of the glass at high redox ratios, e.g., iron redox ratios of 0.4 or greater, particularly 0.5 or greater, due to the formation of iron sulfides (also conventionally referred to as iron sulfides or iron polysulfides). Iron sulfides can form throughout the bulk glass or in streaks or layers in the glass sheet. As used herein, the term "bulk glass" refers to the portion of a piece of glass, such as a glass sheet, that is not chemically altered during the glass formation process. For glass sheets 2 millimeters ("mm") thick or greater produced by the float glass process, the bulk glass does not include the outer region of the glass adjacent to the glass surface, e.g., the outer 25 microns (measured from the glass surface). Removal of gaseous sulfur components in the vacuum refining stage of this known process helps prevent the formation of ferric sulfide in the glass and thus prevents amber coloration.
[0101] As discussed above and shown in Figures 1 and 2, a conventional float glass system typically includes a furnace or melter into which glass material is placed for melting. In one embodiment of the invention, the melting furnace may be an oxy-fuel furnace in which fuel is mixed with oxygen to provide heat for melting the batch materials. In another embodiment of the invention, the melting furnace may be a conventional air-fuel melting furnace in which air is mixed with a combusted fuel to provide heat for melting the batch materials. In yet another embodiment of the invention, the melting furnace may be a hybrid melting furnace in which an oxygen lance is added to a conventional air melting furnace to supplement oxygen to the heated air prior to combustion.
[0102] One difference between glass made from batch materials melted in an oxy-fuel furnace and glass made from batch materials melted in a conventional air-fuel melting furnace is that glass made from batch materials melted in an oxy-fuel furnace typically has a moisture content in the range of 425-600 ppm, whereas glass made from batch materials melted in a conventional air-fuel melting furnace typically has a moisture content in the range of 200-400 ppm, and glass made from 100% cullet melted in an oxy-fuel furnace generally has a moisture content of about 700 ppm. In a preferred embodiment of the invention, the glass batch materials are melted in an oxy-fuel furnace or a conventional air-fuel melter. In the following description of the invention, the invention is practiced using an oxy-fuel furnace, however, the invention is not so limited and any type of glass melting apparatus can be used to practice the invention.
[0103] In the practice of the present invention, typical batch raw materials for making soda-lime-silica glass are introduced into a melting furnace, furnace 20 shown in FIG. 1, furnace 84 shown in FIG. 3. Typical batch materials for soda-lime-silica glass composition include sand, soda ash, limestone, alumina, and dolomite. In one non-limiting embodiment of the present invention, low iron dolomite is used as a batch material. As will be appreciated by those skilled in the art, conventional soda-lime-silica batch materials also include melting and refining aids such as salt cake (sodium sulfate). Salt cake can also be an oxidizer when incorporated into the glass batch. If the salt cake were completely removed from the batch materials, in addition to increasing the difficulty of melting, the redox ratio of the glass would increase to such an extent that polysulfides could form in the bulk glass, which could result in an amber tint to the bulk glass. To control the redox ratio of the glass, a non-sulfur-containing oxidizer could be added to the batch materials in place of the salt cake to oxidize Fe++ to Fe+++ and decrease the redox ratio. One non-limiting example of such a material is sodium nitrate (NaNO3). Sodium nitrate can prevent the redox ratio of the glass from increasing to the point where the bulk polysulfides form, resulting in an undesirable amber tint to the bulk glass, but sodium nitrate can also be used to reduce the amount of NO in the glass manufacturing process.x These emissions can result in the emission of NO x To meet government regulations regarding emissions, melter gases may be treated in conventional manner before being released into the atmosphere.
[0104] A non-limiting embodiment of the present invention is carried out to manufacture the inventive clear glass forming a soda-lime-silica glass composition by the float glass process, characterized by the following formulation based on weight percentages relative to the total weight of the glass, the percentages being obtained using X-ray fluorescence analysis: Weight ratio (%) SiO268~75 Al2O30~5 CaO 5~15 MgO 2~10 Na2O 10~18 K2O 0~5
[0105] In one non-limiting embodiment of the invention, the total iron oxide (Fe2O3) is in the range of 0.02-0.06 wt%, the ferrous iron (FeO) is 0.006-0.02 wt%, the redox (FeO / Fe2O3) is about 0.30-0.55 wt%; Cr2O3 is about 0.3 to 10 ppm; TiO2 is about 50 to 500 ppm; and the reductant percentage of SnO2 is about 10 to 500 ppm, with a critical amount of oxidant SO3 of about 0.10 to 0.25 wt.%. The low iron oxide content is achieved by partially replacing the normal raw material with a low iron raw material, with a maximum content of 0.020 wt.% Fe2O3 when normal dolomite is completely replaced with low iron dolomite.
[0106] In one non-limiting embodiment of the present invention, the low iron dolomite in the batch ranges from 5 to 20 wt% and contains 5 to 15 wt% CaO and 2 to 10 wt% MgO. The low iron dolomite contains about 0.020% or less Fe2O3.
[0107] In one non-limiting embodiment, the transparent glass has a high visible light transmission (L tC); it has a dominant wavelength (DW) of approximately 490-505 nanometers and a purity (Pe) not exceeding 1% for a controlled thickness of 5.66 mm.
[0108] Low-iron transparent glass has a high visible light transmittance and a low iron content, which allows objects seen through the glass to look more beautiful. When used outdoors, it also allows for a brighter, more illuminated space, making it of great importance not only in the architectural industry but also in the automotive industry and applications.
[0109] To achieve the described properties, the present invention provides a suitable balance between ferrous, ferric and chromium oxides, titanium and tin oxides and normal coal or low iron graphite, as well as partial or complete replacement of normal raw materials with low iron raw materials, such as low iron sand with a maximum content of 0.010% Fe2O3, low iron dolomite with a maximum content of 0.020 wt% Fe2O3, low iron calcite with a maximum content of 0.010% Fe2O3, low iron cullet with a maximum content of 0.010% Fe2O3, low iron graphite with a maximum content of 0.010% Fe2O3, etc.
[0110] The desired properties can be achieved by properly balancing the ratio of low iron raw material to clear cullet, but this can be expensive to formulate. It is also possible to achieve the desired properties by using low iron raw material and regular dolomite, but this requires adjusting the ratio of clear to low iron cullet, but this formulation can be expensive.
[0111] Another variable for realizing the glass proposed in this invention is the oxidation-reduction of iron in the glass, using carbon and tin oxide as reducing agents, and sodium sulfate as oxidizing and refining agent. Chromium oxide and titanium oxide are allowed as coloring agents.
[0112] In accordance with the present invention, the above performance characteristics are measured as follows: Light transmittance (L tC) is measured using the CIE Standard Illuminant "C" with a CIE 2° observer in the wavelength range of 380-770 nanometers. The color of glass, in terms of dominant wavelength (DW) and excitation purity (Pe), is measured using the CIE Standard Illuminant "D65" with a 10° observer according to the procedures established in ASTM E 308-2001. Solar ultraviolet total transmittance (T uv ) is 300-400 nm, solar infrared total transmittance (T ir ) is 720~2000 nanometers, and the total solar energy transmittance (T SET ) is measured in the wavelength range of 300 to 2000 nanometers. uv , T ir , T SET The transmittance data was calculated using direct solar radiation data from Parry Moon air mass 2.0 and integrated using the trapezoidal rule as known in the art.
[0113] Also, the CIELAB 1976 color variable L * , a * , b * is calculated using the tristimulus values.
[0114] The glasses of the present invention can be melted and refined in continuous, large-scale commercial glass melting operations and formed into flat glass sheets of various thicknesses by the float process in which the molten glass assumes a ribbon shape and is supported on a pool of molten metal, usually tin, and cooled by methods well known in the art.
[0115] The formulation in Table 1 below has the base batch ingredients, colorants, and redox agents to produce one ton of glass.
[0116] [Table 1]
[0117] Examples 1-7 use low iron raw materials in a non-limiting formulation of the present invention: 0.6 kg of low iron graphite and 5.8 kg of salt cake per ton of glass are added to the batch formulation to control oxidation and reduction in the glass, and a mixture of clear cullet and low iron cullet is used to adjust the iron content.
[0118] Representative raw material compositions in these examples are shown below. [Table 118]
[0119] In Examples 8-16, a blend of low-iron raw materials was used: 0.5 kg of low-iron graphite and 4.3 kg of salt cake per ton of glass were added in batches to control the oxidation-reduction in the glass, and a mixture of clear cullet and low-iron cullet was used to adjust the iron ratio.
[0120] Representative raw material compositions in these examples are shown below. [Table 120]
[0121] Examples 17-21 are formulated with conventional raw materials except for low iron dolomite with a maximum content of 0.020 wt% Fe2O3. 0.5 kg of steam coal and 6.2 kg of salt cake per tonne of glass are added in batches to control oxidation and reduction in the glass. These formulations show that the percentage of Fe2O3 is kept low by substituting low iron dolomite for conventional dolomite and conventional coal for low iron graphite, thereby lowering the cost of the final product. In these examples, recycled cullet is used in the formulations.
[0122] Representative raw material compositions in these examples are shown below. [Table 122]
[0123] Examples 22-30 are batch blended with conventional raw materials, except that low iron dolomite with a maximum content of 0.020 wt% Fe2O3, 0.9 kg of conventional coal and 6.7 kg of salt cake per tonne of glass were added to control oxidation and reduction in the glass. In these examples, low iron dolomite was used to lower the percentage of Fe2O3 in the glass, and therefore the amount of conventional limestone was reduced. Recycled cullet was used in the blends.
[0124] Representative feed compositions for these examples are as follows: [Table 124]
[0125] The following are examples of soda-lime-silica compositions shown in Table 2, which have been shown to provide light transmission (L) at a controlled thickness of about 5.66 mm in accordance with the teachings of the present invention: tC ), ultraviolet (T uv ), infrared (T ir ), total solar transmittance (T SET ) have been reported.
[0126] The compositions of the following glasses were calculated by X-ray fluorescence analysis.
[0127] [Table 2]
[0128] [Table 2]
[0129] [Table 2]
[0130] [Table 2]
[0131] [Table 2]
[0132] Referring to an example from Table 2, a base soda-lime-silica glass composition containing the appropriate balance of chromium and titanium as colorants and low iron graphite or carbon and tin oxide as redox agents. In this composition, the iron oxide is kept in the range of 0.02-0.06 wt% and the sulfate is kept at a critical amount of about 0.10-0.25 wt% so as not to affect the refining properties of SO3. The amount of tin oxide and carbon or low iron graphite added depends on the initial redox conditions of the furnace and the amount of tin oxide required to reach the desired redox in the glass.
[0133] In Examples 1-7, the low iron raw material is a mixture of clear and low iron cullet to achieve the right balance of iron oxide, chromium oxide, and titanium oxide. In these examples, due to the redox conditions present in the furnace, less SnO2 is needed to reach redox in the glass.
[0134] Examples 8 to 16 also contained low-iron raw materials and were mixtures of clear cullet and low-iron cullet, but compared to Examples 1 to 7, the furnace was in a low-oxygen state, so a large amount of SnO2 was added to the glass composition, which was different.
[0135] In Examples 17-21, normal raw materials are used, except for low-iron dolomite. In these examples, the proper balance of colorants such as iron oxide, chromium oxide, and titanium oxide is achieved by using normal sand, in which these oxides are present as impurities. To achieve the required redox in the glass, the amount of SnO2 added varies with the redox conditions in the furnace.
[0136] In Examples 22-30, conventional raw materials are also used, except for low iron dolomite. In these examples, the amount of low iron dolomite is increased and the amount of conventional limestone is decreased relative to the previous examples. Also, the amount of SnO2 is varied as required by the redox conditions in the furnace. As with Examples 17-21, the proper balance of the colorants described can be achieved by using conventional sand.
[0137] Examples 1-21 from Table 2 maintained TiO2 at about 50-500 ppm. The titanium oxide in the above range improves the light transmission through the glass, which is one of the main features of the proposed glass. Furthermore, excess titanium oxide imparts a yellowish tint to the glass.
[0138] It will be understood by those skilled in the art that when iron oxide, titanium oxide or chromium oxide are present in amounts greater than the ranges mentioned, the light transmittance will drop to values lower than those suggested in this patent.
[0139] The addition and control of these materials provides a transparent glass according to a non-limiting embodiment of the present invention, which includes about 0.02 to 0.06 wt.% total iron oxide (Fe2O3), 0.006 to 0.02 wt.% to 0.02 wt.% ferrous iron (FeO), about 0.30 to 0.55 redox (FeO / Fe2O3), about 0.3 to 10 ppm Cr2O3, about 50 to 500 ppm TiO2, about 10 to 500 ppm SnO2, and about 0.10 to 0.25 wt.% SO3. At a controlled thickness of 5.66 mm, the example glass has a visible light transmission (L tC ), having a dominant wavelength (DW) of about 490 to 505 nanometers and a purity (Pe) not exceeding 1%.
[0140] The compositions disclosed herein are produced by a float process in a range of about 1 millimeter to 25 millimeters.
[0141] Having reached the proposed properties for the transparent glass composition, other modifications may be applied according to the scope of the invention without departing from what is set forth in the following claims. Accordingly, the specific embodiments detailed herein are illustrative only and do not limit the scope of the invention, which is to be given the full breadth of the appended claims and any equivalents thereof.
Claims
1. 1. A glass composition comprising: 【Table 9】 Furthermore, the glass composition is formed from a glass batch containing 5 to 20 wt % low-iron dolomite, and the low-iron dolomite is 2 O 3 The glass composition has a total iron content, expressed as content, of less than 0.1 wt.%, a total CaO content of 30-35 wt.%, and a MgO content of 15-25 wt.%.
2. Fe 2 O 3 is in an amount of 0.021 to 0.053 wt %, and the redox ratio (FeO / Fe 2 O 3 2. The glass composition of claim 1, wherein the coefficient of friction (T) is in the range of 0.30 to 0.
46.
3. The glass composition contains 0.005 to 0.05 wt % TiO 2 The glass composition of claim 1 further comprising:
4. The glass composition has a light transmittance (L TC ); less than 90% ultraviolet transmittance (T uv ); infrared transmittance (T IR ); total solar energy transmittance (T SET ); Lightness value (L * ) 90-99; a * Color channel 1 to -2; b * 10. The glass composition of claim 1, which can be utilized to produce a glass having color channels 1 to -1; a dominant wavelength of 470 to 525 nm; and a purity (Pe) of 2% or less.
5. The glass composition contains 0.0025 to 0.05 wt % SnO 2 The glass composition of claim 1 further comprising:
6. 10. The glass composition of claim 1, wherein the source of iron further comprises one or more low iron materials selected from low iron sand, low iron limestone, low iron clear cullet, or combinations thereof.
7. Low-iron dolomite is 2 O 3 2. The glass composition of claim 1 having a total iron content, expressed as content, of less than 0.030 wt.-%.
8. Low-iron dolomite is 2 O 3 10. The glass composition of claim 1 having a total iron content, expressed as content, of less than 0.020 wt.
9. the below described: Blending raw materials, the raw materials comprising cullet, sand, soda ash, salt cake, limestone and dolomite, the dolomite comprising: 【Table 1】 melting the raw materials to form a molten glass; pouring the molten glass onto a bath of molten tin; moving the molten glass over the surface of the molten tin bath while controllably cooling the molten glass and applying a force to the molten glass to form glass of a desired thickness and a desired width; and removing the glass from the molten bath; 1. A method of forming transparent glass comprising: Moreover, the dolomite is low-iron dolomite, Moreover, the glass batch has an Fe content within the range described in the above table. 2 O 3 A method for forming a transparent glass comprising 9-18 wt. % low iron dolomite having a total iron content expressed as a percentage.
10. 10. The method of claim 9, wherein the ingredients are present in the following amounts: 【Table 2】
11. 10. The method of claim 9, wherein the sand comprises: 【Table 3】
12. 10. The method of claim 9, wherein the salt cake comprises: 【Table 4】
13. 10. The method of claim 9, wherein the cullet comprises: 【Table 5】
14. 10. The method of claim 9, wherein the limestone comprises: 【Table 6】
15. 10. The method of claim 9, wherein the soda ash comprises: 【Table 7】
16. 10. The method of claim 9, wherein the feedstock further comprises coal or graphite.
17. 17. The method of claim 16, wherein the coal or graphite is in the range of 0.01 to 0.3 wt %.
18. 17. The method of claim 16, wherein the coal or graphite comprises: 【Table 8】